2007
DOI: 10.1177/0003319706294555
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Cigarette Smoking on Heart Rate Variability

Abstract: Acute cigarette smoking enhances adrenergic activity and thus may be associated with hemodynamic changes in the cardiovascular system. In this study, the acute effect of cigarette smoking on heart rate variability (HRV) was studied. Fifteen subjects were included in the study. Time domain (the mean R-R interval, the standard deviation of R-R interval, and the root mean square of successive R-R interval differences) and frequency domain (high-frequency, low-frequency ratio, and low-frequency/high-frequency rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
62
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 27 publications
15
62
0
3
Order By: Relevance
“…Decrease in the vagal modulation during smoking was also observed by Karakaya et al 11 , who evaluated the acute effects of smoking in 15 nonsmoker volunteers on HRV indices and observed changes in the TD and FD, particularly in the 5-10 minutes immediately after the act of smoking, characterized by a decrease in the SDNN, RMSSD and HF indices, as well as an increase in the LF index. Nabors-Oberg et al 30 equally verified a decrease in the HF index during smoking.…”
Section: Discussionsupporting
confidence: 64%
“…Decrease in the vagal modulation during smoking was also observed by Karakaya et al 11 , who evaluated the acute effects of smoking in 15 nonsmoker volunteers on HRV indices and observed changes in the TD and FD, particularly in the 5-10 minutes immediately after the act of smoking, characterized by a decrease in the SDNN, RMSSD and HF indices, as well as an increase in the LF index. Nabors-Oberg et al 30 equally verified a decrease in the HF index during smoking.…”
Section: Discussionsupporting
confidence: 64%
“…As early as (Elliott, 1968) it was proven that cigarette smoking caused elevations in HR of about 20 bpm. Study by (Karakaya, 2007) showed that cigarette smoking alters heart rate variability [HRV] parameters, particularly within the first 5 to 10 minutes after smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with findings described in previous studies in which changes in heart rate variability indexes were found in the time and frequency domains after cigarette smoking. 55 Acute changes in cardiac autonomic control induced by smoking are mostly attributed to nicotine, which stimulates the release of catecholamines (norepinephrine and epinephrine) through activation of nicotinic receptors located on sympathetic nerve endings and the adrenal glands, causing widespread adrenergic stimulation at the peripheral level. 56 The combination of both stimuli led to a significant reduction in all heart rate variability indexes, except LF (normalized units), HF (normalized units), and the LF/HF ratio.…”
Section: Cardiac Autonomic Modulation Responsementioning
confidence: 99%